Naturalized reptiles and amphibians of the world - Lever, Christopher (Oxford University Press, 2003)
This book describes how the various alien reptiles and amphibians now living in the wild throughout the world were first introduced, how they subsequently became naturalized, their present distribution and status in those countries to which they were introduced, and their ecological and socio-economic impact on the native biota and local economies. Many species have had a more or less neutral impact, being neither beneficial nor harmful. However, several have had a positive ecological or socio-economic impact, while some such as the cane toad, have had an extremely destructive effect.The criteria for inclusion of a species are that it should have been imported from its natural range to a new country by human agency--either accidentally or deliberately--and that it should currently be established in the wild in self-maintaining and self-perpetuating populations unsupported by and independent of mankind